Innovative Funding Synergy for Optimizing Land and Building Waqf Utilization in Islamic Philanthropy Programs - Galeh Pujonegoro; Kharis Nugroho; Pitri Yandri (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
One of the problems Nazhir faces in realizing the benefits of immovable asset waqfs, such as land and buildings, is funding. Not all asset waqf handed over by wakif are in top condition. On the other hand, nazhirs feel an obligation to facilitate wakif worship. It finally requires Nazhir to be able to raise funds to improve asset quality according to program planning, so that the waqf assets can be widely useful for the community and generate value that continues to flow. This paper reviews the asset-based waqf program funding model that is useful for realizing the nazhir waqf program. This study looked at three nazhirs, namely Baitulmaal Muamalat, Dompet Dhuafa, and BSI Maslahat, located in Jakarta. The research method uses an observational design with in-depth interview instruments. This research found that Nazhir, which also has Zakat institutions, strategically has a broad program funding model. In addition to the single waqf instrument model (direct-indirect) and the capital participation model by angel investors, one of the models that is also applied is to integrate waqf funds and ZIS (Zakat, Infak, Sadaqah) through the involvement of Zakat institutions. The three nazhirs implemented a policy of synergy and collaboration in funding the waqf program as part of the solution to generate benefits for the asset-based waqf program. The implementation of ZISWAF fund integration provides additional breadth of funding sources for Nazhir to realize its program, which in the end is not limited only to waqf instrument fund sources, such as waqf in the form of money, stock waqf, cash waqf linked to sukuk, and so on. Technically, Zakat institutions distribute ZIS funds to asset-based programs at their nazhir institutions while still paying attention to the principles of program accuracy, recipients, and asnaf.